Cultivating Religious Character in Eight-Grade Student at MTs Darul Maarif Purwodadi for the 2024/2025 Academic Year - Ibnu Faiz Mubarok; Shokhibul Mighfar; Muhammad Munadi (Konsultan Jurnal Ilmiah Indonesia, 2025)
The large number of students from diverse backgrounds and with varying characters, such as a lack of politeness toward teachers and parents, students who still violate the rules in the madrasah environment, and a low level of religious character awareness. The purpose of this study is to determine the cultivation of religious character in eighth-grade students at MTs Darul Ma'arif Purwodadi. This study uses a descriptive qualitative approach. It will be held at MTs Darul Ma'arif from November 2024 to April 2025. Data collection methods used observation, interviews, and documentation. Data validity was ensured using source and method triangulation. The data was then analyzed using an interactive model with data reduction, data presentation, and conclusion drawing steps. The results of this study indicate that the cultivation of religious character at MTs Darul Ma'arif is carried out thru the habituation of reading Asmaul Husna, Quran Reading and Writing (BTQ), Dhuha and Dhuhr prayers in congregation, and Quran recitation, which are carried out according to a regular weekly schedule. Asmaul Husna habituation is done every Friday and Saturday under the supervision of teachers and led by students on a rotating basis, creating a solemn learning atmosphere despite some minor discipline issues. BTQ learning emphasizes memorizing short surahs from Juz 'Amma using the tartil method and makhorijul huruf, which are closely supervised by the teacher who also serves as a role model for religious behavior for the students.